A IMPLANTAÇÃO DE INCUBADORAS DE EMPRESAS: ESTUDO DE CASO DE UMA CIDADE DO INTERIOR PAULISTA - Bernardes, Marco Aurelio (2009)
The research deals with the study of the deployment of an incubator of companies in the municipality of Santana de Parnaiba in 2005. Two structured questions to research: What factors or social and economic indicators, as provided for in the National Program Support for Implementation of Business Incubators, is shown as enablers, or not, to choose the type of incubator located in the city? The incubator of Santana de Parnaiba is not configured or as a set of economic and social development? These guiding questions determined the general objective of the study and the specific objectives were to investigate whether or not the application of Technical Feasibility Studies and Economic/SEBRAE; raise the socioeconomic profile of the local enterprise, and identify the profile of companies graded as the generation of jobs. To meet the goals it was decided to conduct the search qualitative descriptive and exploratory in nature. The strategy of participant observation was followed from the field of consulting the diaries and primary and secondary sources, with the reading and consultation of documents and records in the archives of the deployment FIESP. As part of the strategy for data collection was applied, with the world of research, business and executive coordinator of the Program for Incubators FIESP, roadmap semi - structured issues. Data were analyzed by technique of content analysis, following the methodology of the Case Study. Served as a ground conductor to note that the remarkable development of technology provided by the capitalist system, the advancement of production processes and increase productivity in large corporations and were still significantly higher rate occurring in the dynamics of training and qualification of the workforce in countries in development, which is growing unemployment and informality. The recent American crisis in 2008 set the opportunity for better understanding of the concept of incubators and other joint ventures. The research results indicate that all entrepreneurs have received basic information-key marketing and finance. The support of specialized consultants, participation in fairs and developing the business plan during the incubation of enterprises covered expectations of technology spread. The research indicates that technology-based ventures in the incubator resulted not effective support the demands for new processes and new products. That was the answer to the deficit targets for generation of employment in the locality by the three technology-based companies located in the incubator. The results indicate that despite the significant amount of normative content of documents dealing with the prevention of failures of public policies to support the establishment of incubators and entrepreneurship, we could not find evidence of links between economic development and social development and feasibility studies Technical and Economic preceding the establishment of the incubator in the city studied.(AU)